To Examine the Pattern of Ensuring the Reliability of The NGN Network - Najbiddinov Nodirbek Burhonovich; M.B. Abdujapparova; Hojiyev Suhrob (Zien Journals, 2021)
This article summarizes the main points of the algorithm and program for calculating the structural reliability of the NGN network using a statistical simulation method, which allows the designer for a short time to analyze the reliability of the designed network.
Keywords: Next-Generation Network; Key Architectural; algorithm; calculating